Retextualização do gênero entrevista: refletindo sobre os usos da língua materna - Nádia do Rosário Duarte (2016)
This term paper investigated how elementary students of the 6th grade of a military school understand and process information when practicing retextualization by using the interview genre. Through this study, students performed various activities: they answered questionnaires, undertook research and collective discussions to make decisions, created questions, conducted interviews with guests (people connected to the institution Colégio Militar de Belo Horizonte) and recorded them on video and audio. They transcribed the speech of the respondents and retextualized the interviews, which were printed and then published on the school website. This work was anchored in a qualitative approach, and more specifically, it is a study case. The teacher-researcher made the monitoring of activities through field diaries and recorded classes, enabling aspects of school past history were made present, showing the memory of the respondents. All this allowed the establishment of dialogical relations of great social value and highlighted the importance of working with the discursive / textual genres in the classroom. The data generated in this research testified that the students of the 6th grade comprise the two types of language - oral and written, expressed in the interview genre. This work is an invitation for teachers, especially those of elementary school, so that they run practices that enable students to understand the speech-writing relationship. By doing so, the Portuguese Language classes will make more sense to students, notwithstanding the fact that they will be providing tools for the students undertake social practices. After all, our daily communication occurs primarily through orality.